Unveiling the origin of the large coercivity in (Nd, Dy)-Fe-B sintered magnets - Xin Tang; Jiangnan Li; Hossein Sepehri-Amin; Anton Bolyachkin; Andres Martin-Cid; Shintaro Kobayashi; Yoshinori Kotani; Motohiro Suzuki; Asako Terasawa; Yoshihiro Gohda; Tadakatsu Ohkubo; Tetsuya Nakamura; et al. (NPG Asia Materials, 2023)
Abstract Nd-Fe-B-based permanent magnets are widely used for energy conversion applications. However, their usage at elevated temperatures is difficult due to the relatively low coercivity (H c) with respect to the anisotropy field (H A) of the Nd2Fe14B compound, which is typically 0.2H A. In this work, we found that the coercivity of an (Nd0.8Dy0.2)-Fe-B sintered magnet could reach 0.4H A, which was twice as high as the H c/H A of its Dy-free counterpart. Detailed microstructural characterizations, density functional theory and micromagnetic simulations showed that the large value of coercivity, H c = 0.4H A, originated not only from the enhanced H A of the main phase (intrinsic factor) but also from the reduced magnetization of the thin intergranular phase (extrinsic factor). The latter was attributed to the dissolution of 4 at.% Dy in the intergranular phase that anti-ferromagnetically coupled with Fe. The reduction in the magnetization of the intergranular phase resulted in a change in the angular dependence of coercivity from the Kondorsky type for the Dy-free magnet to the Stoner–Wohlfarth-like shape for the Dy-containing magnet, indicating that the typical pinning-controlled coercivity mechanism began to show nucleation features as the magnetization of the intergranular phase was reduced by Dy substitution.